PELAKSANAAN TUGAS DINAS PENGENDALIAN PENDUDUK, KELUARGA BERENCANA, PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK DI KABUPATEN KUANTAN SINGINGI TAHUN 2023-2024 - Bestario, M. Dava; ,, Wazni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This research is motivated by the phenomenon of violence against children in Kuantan Singingi Regency which has been increasing every year. The DP2KBP3A is responsible for preventing violence against children in the Kuantan Singingi Regency area. The number of cases increased from 12 cases in 2022, an increase of 15.38% to 15 cases in 2023, and in 2024 increased by 166.67% to 40 cases. With the phenomenon of increasing cases of violence against children, government action is needed to prevent acts of violence against children. This research aims to describe the implementation of the duties of DP2KBP3A in accordance with the Regulation of the Regent of Kuantan Singingi Number 72 of 2021. This research uses a qualitative approach and a descriptive research type. This research uses primary data obtained from research informants and is supported by secondary data obtained from official government documents and scientific publications. The data collection techniques in this research use interview and documentation techniques. The research findings indicate that the implementation of tasks by DP2KBP3A in the formulation and execution of technical policies, supervision, evaluation, and reporting can be considered optimal. However, the execution of tasks in coordination, facilitation, and guidance cannot yet be considered optimal. This is due to the fact that coordination conducted by DP2KBP3A with village governments, schools, and horizontal institutions is still limited. The guidance provided can be said to be suboptimal, primarily due to the lack of training received by employees regarding violence against children. The facilitation offered is still not optimal, as there is a lack of supporting facilities provided by DP2KBP3A to prevent violence against children. Keywords: DP2KBP3A, Violence against children, Implementation of duties, Prevention of violence against children, Child protection